Comparison of pregnancy outcomes of frozen embryo transfers in women undergoing artificial endometrial preparation with and without short and long-acting gonadotropin releasing hormone agonists - Marzieh Mehrafza; Tahereh Zare Yousefi; Sahar Saghati Jalali; Zahra Nikpouri; Azadeh Raoufi; Elmira Hosseinzadeh; Sajedeh Samadnia; Ahmad Hosseini (Mashhad University of Medical Sciences, 2019)
Background & aim: There are conflicting results regarding the benefit of gonadotropin releasing hormone (GnRH) agonist treatment on frozen embryo transfer (FET) outcome. No study was found to compare pregnancy outcome between patients undergoing short and long acting types of GnRH agonist for FET cycles. This study aimed to assess the effectiveness of short and long acting GnRH agonist on FET cycle outcomes. Methods: The present retrospective study was conducted on 296 patients who underwent FET cycles between 2016 and 2017 at Mehr Medical Institute, Rasht, Iran. Pregnancy outcome were compared among three groups: Group A (n=103) received artificial hormone-mediated cycles without GnRH agonists, Group B (n=100) and C (n=93) received artificial hormone-mediated cycles with short and long-acting GnRH agonists, respectively. Also 16, 26, 12 polycystic ovarian syndrome (PCOS) patients (in group A, B and C respectively) were also assessed for ongoing pregnancy rate among three groups. Data were analyzed using analysis of variance, Kruskal-Wallis, Chi-square goodness of fit test and multivariate logistic regression. Results: No statistically significant differences were observed in terms of endometrial thickness (p=0.053), implantation (p=0.94), biochemical (p=0.67), clinical (p=0.82) and ongoing (p=0.96) pregnancy rates in three groups. Also, PCOS patients did not show significant differences in ongoing pregnancy rate among three groups (p=0.72). Conclusion: The findings revealed that neither non- PCOS nor PCOS patients undergoing artificial hormone-mediated endometrial preparation benefit from the addition of short or long-acting GnRH agonist to FET cycles.